MEDIA TAK-TIK KOPER UNTUK MENINGKATKAN KETERAMPILAN MENYELESAIKAN MASALAH SPLDV KELAS VIII-A SMPN 4 ACEH TAMIANG - Kurnia Rahmianum (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2019)
Learning mathematics using media of tak-tik koper is an innovation in solving SPLDV problems with a short case, uncomplicated manner, and a reasonable level of accuracy. Tak-tik koper is an acronym of confident, that is made of (1) cardboard or stereo form as a base board, (2) colorful papers as cards which is written numbers for coefficients, symbols of operation, and letters for variables, (3) pins as adhesive. By means of this media, it will produce a solution based on cross multiplication, so that it will be obtained a general formula as another way to solve the problems of the two variables linear equations system (SPLDV). Based on the purpose of using the media of tak-tik koper, is to improve the skills and activeness in solving SPLDV problems for students of VIII-A grade at SMPN 4 Percontohan for the 2018/2019 academic year, which results in a classical increase for the student's mastery of learning from 16,13% during the learning which did not use the media of tak-tik koper to 90.32% at the end after using the media of tak-tik koper during the learning process and an increase in the percentage of the average score of student’s activities by 8.34%.